Investigation of Possible Reasons of Failed Treatment of Conservative Thoracolumbar Osteoporotic Vertebral Fractures - Ozdemir, Mustafa Abdullah; Bayram, Serkan; Karalar, Sahin; Korkmaz, Murat; Sulejmani, Iljhan; Sivacioglu, Sevan; Akgul, Turgut (Turkish neurosurgery, 2023)
To investigate the possible reasons of failed conservative treatment of osteoporotic thoracolumbar vertebral compression fractures (VCFs). Sagittal balance impairment may weaken union by increasing the load on the fracture line. Most osteoporotic vertebral fractures occur in the thoracolumbar and mid-thoracic regions. We investigated the records of patients aged > 60 years who underwent treatment for osteoporotic thoracolumbar VCFs between 2012 and 2020. The patients were divided into two groups: those who required surgical treatment due to the failure of conservative treatment and those who were successfully treated with conservative treatment. All the patients underwent lateral radiography and computer tomography of the whole spine at their initial and final visit. The radiographic parameters of spine and presence of sarcopenia, age, and gender were compared between the groups. Of the study subjects, the mean age of 13 females and 7 males in whom conservative treatment was successful was 67.4 years and the mean follow-up period was 23.5 months, while in 18 females and 5 males who underwent surgical treatment due to the failure of conservative treatment, the mean age was 68.7 years and the mean follow-up period was 22.1 months. No significant differences between the groups regarding age and gender were observed. However, significant differences were observed between the groups regarding the presence of sarcopenia and thoracic kyphosis, thoracolumbar kyphosis and distance from the center of the fractured vertebra to the plumb line (DSVA). Sarcopenia and DSVA were significantly higher in the surgical treatment group. Receiver operating characteristic analysis demonstrated that the sensitivity and specificity of DSVA for identifying high-risk patients for failed conservative treatment of osteoporotic thoracolumbar VCFs were 100% and 95%, respectively, with an optimum diagnostic cutoff value of 6.5 mm.